Perlindungan Hukum terhadap Pengguna Jasa Angkutan Sewa Umum di Provinsi Bali - Made Bayu Anggara; I Nyoman Sujana; Ni Made Puspautari Ujianti (Warmadewa Press, 2021)
Transportation is a very important field of activity in providing transportation services. The need for transportation (public transportation) is increasing, urban areas are expanding where the pattern of movement has covered the inter-region of Bali Province. Transportation of people with motorized vehicles that do not have a route is regulated by Regulation of the Minister of Transportation Number 108 of 2017 concerning the Implementation of transportation of people with public motorized vehicles that are not on routes. This study aims to analyze the implementation procedures for the implementation of public rental transportation in Bali Province and how the legal protection for public rental transportation service users in Bali Province. This study uses normative legal research methods, namely by examining library legal materials or primary materials and secondary data. The approach used is a statutory approach. The results showed that the regulation on consumer protection has been regulated in Law Number 8 of 1999 concerning consumer protection, hereinafter referred to as UUPK. Legal protection for users of public rental transportation services has referred to Law Number 8 of 1999 concerning consumer protection whereas business actors should provide the best service to consumers for the sake of mutual comfort and good.